2020
DOI: 10.1371/journal.pntd.0008024
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomine sand flies and Leishmania species in a focus of cutaneous leishmaniasis in Algeria

Abstract: Cutaneous leishmaniasis is a disease caused by various Leishmania spp., which are transmitted by phlebotomine sand flies. Algeria is one of the most affected countries, with thousands of cutaneous leishmaniasis cases registered every year. From March to November of 2016 and 2017, sand flies were collected in 12 municipalities in Setif province, NorthEastern Algeria. Sand flies were identified and females were tested by PCR for detecting Leishmania DNA. Additionally, cutaneous leishmaniasis cases notified durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…The same observations were made in the study conducted by Zait and Hamrioui in 2009, who explained that the seasonal effect of leishmaniasis cases was linked to the seasonal dynamics of the vectors and the incubation period of the disease, i.e., the signs of the disease (skin lesions) appear one to two months or more after the infecting bite by female sandflies. In Algeria, sandflies have different peaks of activity, depending on the species and region of interest, with the peak occurring in the summer and autumn [8,9]. This study revealed that the age group most affected was the under10s (200 patients), which is in line with the results of other studies showing that CL lesions mainly affect preschool children [2].…”
Section: Discussionsupporting
confidence: 86%
“…The same observations were made in the study conducted by Zait and Hamrioui in 2009, who explained that the seasonal effect of leishmaniasis cases was linked to the seasonal dynamics of the vectors and the incubation period of the disease, i.e., the signs of the disease (skin lesions) appear one to two months or more after the infecting bite by female sandflies. In Algeria, sandflies have different peaks of activity, depending on the species and region of interest, with the peak occurring in the summer and autumn [8,9]. This study revealed that the age group most affected was the under10s (200 patients), which is in line with the results of other studies showing that CL lesions mainly affect preschool children [2].…”
Section: Discussionsupporting
confidence: 86%
“…The factorial plane displays that P. papatasi is the main contributor of the F1 inertia, and its abundance correlates with arid steppe, plains, and foothills, and less frequently with mountains (9.3%). Steppes offer optimal ecological conditions for this species [ 7 , 24 , 38 , 39 ]. Phlebotomus perniciosus and P. longicuspis are the main contributors to the axis 2 inertia.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence (OC) is the ratio of the number of collections where species occur and the total number of collections [27]. This parameter, according to Gherbi et al [28], enables patterns of Culicoides species distribution to be classified into five categories, as follows: (i) sporadic (OC ≤ 20%), (ii) infrequent (OC > 20% but ≤40%), moderate (OC > 40% but ≤60%), frequent (OC > 60% but ≤80%), and constant (OC > 80%). Two diversity indices, Shannon H' index and evenness (E), were estimated for the three habitat types using PAST version 1.81 [29].…”
Section: Discussionmentioning
confidence: 99%